Norfolk Island Penal Colony - Finnane, Mark (ADA Dataverse, 2021)
A reconstructed register of convicts detained at the Norfolk Island Penal Colony. Data was prepared by Dr Tim Causer (University College London) and curated for the Prosecution Project by Mark Finnane and Lisa Durnian.